Pengaruh dan Manfaat Gerakan Literasi Terhadap Pemahaman Bahasa: Meningkatkan Kompetensi Linguistik di Era Digital - Andri Muharrodin Nata; Farid Alfajri Nur Insani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The literacy movement plays a crucial role in enhancing language comprehension and linguistic competence, especially in today’s digital era. This study aims to explore the influence and benefits of literacy movements on language comprehension across various segments of society. Through qualitative and quantitative approaches, this research examines how participation in literacy activities such as reading, writing, and group discussions can improve language skills, enrich vocabulary, and enhance communication abilities. The findings indicate that literacy movements not only help individuals understand and use language more effectively but also foster critical thinking and creativity. Furthermore, the growing digital literacy provides broader access to educational resources and information, thus strengthening language comprehension in a wider context. Therefore, literacy movements contribute significantly to building a more knowledgeable and insightful society.